Komponentontleding as leksikografiese instrument - Vos, I.L. (Lexikos, 1993)
Componential Analysis as Lexicographical InstrumentOne of the most important functions of descriptive dictionaries is to convey semantic information. The lexical meaning of a collection of lexical items must be defined according to certain semantic norms. One of the lexicographer's major problems is that inadequate semantic norms have been identified and defined for the introduction of encyclopedic information into standard dictionaries. It is for example generally accepted that encyclopedic information has no place in descriptive dictionaries because it describes extralinguistic reality, while descriptive dictionaries should be confined to language. Nevertheless, a complete, clear and unambiguous conveyance of meaning sometimes requires that a certain amount of encyclopedic information should be incorporated in the elucidation of meanings. The lexicographer needs practical guidelines in order to accomplish a proper conveyance of meaning. Componential analysis can be regarded as an instrument through which the lexicographer can differentiate between components that convey lexical meaning and components that are supplementary and therefore redundant. Although valid objections can be raised to certain aspects of componential analysis, it should not be completely discarded as a lexicographical instrument. The shortcomings and possible insufficiencies of componential analysis should rather be regarded as a stimulus to enhance the co-operation between the linguist and the lexicographer.